(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
The role of plant-based nutrition for dietary health in Nigeria has been recognized. The nutritional challenges both globally and in Nigeria are increasing while the world is becoming more aware of the impact of malnutrition and global efforts are increasingly concentrating on addressing malnutrition and increasing food security. Diets affect nutrition and health outcomes and thus have social, economic, and environmental impacts. Nutraceuticals are food or food-derived products with additional characteristics to minimize the occurrence and prevention of certain chronic diseases. They include dietary fibre, probiotics, prebiotics, polyunsaturated fatty acids, antioxidant vitamins, carotenoids, polyphenols, spices, fruits, and vegetables that have proven to have potential health benefits. The link between plant-based nutrition and overall health and well-being is already gaining momentum as a diet rich in plant-based foods and with fewer animal-source foods confers both improved health and environmental benefits. At the same time, an increased intake of fruits, vegetables, nuts, and whole grains has been associated with a lower incidence of mortality due to cardiovascular diseases. This study advocates for leveraging plant-based nutrition in Nigeria to address health and nutrition challenges. Recommendations include targeted education and supportive policies for widespread adoption, fostering improved public health.